2016
DOI: 10.18632/oncotarget.13384
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA GAS5 contributes to lymphatic metastasis in colorectal cancer

Abstract: Colorectal cancer (CRC) ranks the third most common type of cancer worldwide. However, the detailed molecular mechanisms underlying these processes are poorly understood. Recent studies have shown that lncRNAs play important roles in carcinogenesis and progression of CRC. The lncRNA growth arrest special 5 (GAS5), was previously identified to be down-regulated and functions as a tumor suppressor gene in many kinds of cancers. In current two-stage, case-control study, we systematically evaluated the potential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 49 publications
4
67
0
Order By: Relevance
“…In some complex diseases (including cancer, neurological diseases and diabetes mellitus), lncRNA expression levels are increased or decreased. 12,13 Such dysregulated expression could have an important role in both the pathogenesis and progression of a disease through various pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In some complex diseases (including cancer, neurological diseases and diabetes mellitus), lncRNA expression levels are increased or decreased. 12,13 Such dysregulated expression could have an important role in both the pathogenesis and progression of a disease through various pathways.…”
Section: Introductionmentioning
confidence: 99%
“…A CCAT1‐specific peptide nucleic acid‐based molecular beacon was reported to serve as a powerful diagnostic tool for the specific identification of colorectal cancer . GAS5 is associated with not only susceptibility to colorectal cancer but also the metastasis of colorectal cancer to the lymph node .…”
Section: Discussionmentioning
confidence: 99%
“…23 GAS5 is associated with not only susceptibility to colorectal cancer but also the metastasis of colorectal cancer to the lymph node. 24 SLCO1B3, a solute carrier organic anion transporter family member, is upregulated in colorectal cancer. 25 The overexpression of SLCO1B3 changed p53-dependent pathways and conferred apoptotic resistance in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We have described these in a previous study which evaluated the functional of LncRNA GAS5 in development and progression of CRC [19]. Five milliliter peripheral blood was collected from all subjects, and demographic information were face to face interviewed by the project staff.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we identified that the allele del of lncRNA GAS5 rs145204276 was significantly associated with 21% decreased risk of CRC [19]. Carriers of allele del are less likely to get lymph node metastasis, which should that GAS5 rs145204276 were significantly associated with the susceptibility and progression of CRC [19].…”
Section: Introductionmentioning
confidence: 99%